Formación integral directiva (2018)
This research aims to address the problems that an organization has on the integral formation that is presented in the management of organizations, based on topics of human talent, organizational climate, organizational culture, emotional intelligence, leadership, work teams, among others. Concerning research, it is intended to design and implement approaches that help integral training to be more efficient and competitive than top management should take, seeking to improve the socio-affective, communication, spiritual and cognitive aspects.